Comparative assessment of the fracture resistance of endocrowns fabricated from three different CAD/CAM ceramic blocks - Maryam Ansari; Marzieh Alikhasi; Negin Yaghoobi; Nikfam Khoshkhounejad (Journal of Dental Materials and Techniques)
Objective: This study aimed to compare the fracture resistance of endocrowns fabricated from three different computer-aided design/computer-aided manufacturing (CAD/CAM) ceramic materials.Methods: A maxillary left first molar of a typodont model was scanned using an intraoral scanner both before and after standardized endocrown preparation. The scan of the prepared tooth was used to fabricate thirty-six identical resin dies through three-dimensional printing. These dies were then assigned to three groups (n=12), each corresponding to a different CAD/CAM ceramic material: IPS e.max CAD, VITA Suprinity, and VITA Enamic. Endocrowns were digitally designed and milled for each group using a CAD/CAM system. They were then cemented onto the resin dies with dual-cure resin cement and subjected to 5000 thermal cycles. A compressive load was applied to each specimen at a 35° angle to the palatal cusp using a universal testing machine until fracture occurred. Fracture resistance values were recorded in Newtons, and failure modes were evaluated by a stereomicroscope. Statistical analysis was performed using the Kruskal-Wallis, Mann-Whitney U, and Bonferroni tests (P<0.05).Results: A statistically significant difference was found in the fracture resistance among the three groups (P=0.01). The IPS e.max CAD group exhibited significantly higher fracture resistance compared to the VITA Enamic group (P=0.01). No statistically significant difference was observed in failure modes across the groups (P>0.05).Conclusions: Endocrowns fabricated from IPS e.max CAD demonstrated the highest fracture resistance with no cases of catastrophic failure. VITA Suprinity endocrowns showed the second-highest fracture resistance, with only one case of catastrophic fracture.